Political party as a derivative of the TV show in contemporary Ukraine: cultural technology of image versus ideology - O. Y. Pavlova (Ukrainian Cultural Studies, 2022)
The author analyzed the TV show "Servant of the People" and how it influenced the functioning process of political parties in Ukraine through the prism of the correlation of ideological and technological practices in the TV show. The methodology of the study is based not on the analysis of the content of political programs and organizations, but on the logic of hierarchies and transformations of cultural practices. The main marker of the dominance of technology over ideology in the 2019 presidential elections in Ukraine was the fact that a political party is created with the same name after it became clear that the success of the show ensured the victory of the protagonist’s representative in the elections. Mass media is a form of cultural power of an ever-expanding group of educated people. It combines the elements of ideology and technology of image. The historical dynamics of the mass media demonstrates several historical stages in this process. The first stage is the print media: the text-centrism of this media creates an ideological dominant for unifying into large enough groups of people at the cost of the regulative idea of rational discourse. The decentralization of political positions, represented as variety of political parties, is carried out as rational criticism. The second stage is optical media (cinema and television): the circulation of images from this period creates a positive emotional connection to the political leader beyond the mediations of the rational bureaucracy. The dramaturgical style of media criticism does not assume an active position of a rational subject, but a passive mass viewer, who expresses an evaluative position on professionally produced images, including images of the political sphere. The technology of image production dominates the ideological narrative. The third stage is the reproduction of optical media in Internet practices. Here the simplification of production and circulation, of discourse and image, leads to a new level of immediacy in the connection between the political leader and his voters, on the one hand. On the other hand, the political, as well as other elite spheres, are beginning to lose their privileged status in the democratization of cultural capital production. Internet media suggest a de-differentiation of image and discourse, ideology and technology of image. There is a certain imbalance towards the production of images above narrative.